The The Curricullum and Educational Politics - Azmi, Ulul; Mahdi; Zuhdi, Muhammad; Rozak, Abdul (MATAAZIR: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
This study aims to describe the curriculum and education politics, the goals and functions of education politics, political and educational relations, state control over education, and a sketch of education politics in Indonesia. This study uses the literature study method, based on references from sources related to the research theme used as a reference. The results of this study indicate that the curriculum is the main part of education. Education and politics are two important elements in the socio-political system in every country, both work hand in hand in the process of forming the characteristics of society in a country. State control over education is carried out in four ways, namely: first, the education system is regulated legally; second, the education system is run as a bureaucracy, emphasizing adherence to rules and objectivity; third, implementation of compulsory education; fourth, political and economic reproduction that takes place in educational institutions in a particular political context. The sketches in Indonesian education are divided into 6 periods starting from the beginning or prehistory to the present. In addition, all policies related to education issued by the government are products of educational politics. On the other hand, the government is also obliged to ensure that all people get proper education, so that it hopes to produce quality human resources and can contribute to the interests of the nation and state. Key Word: Curricullum, Education, Educational Politics.